2006
DOI: 10.1111/j.1399-3054.2006.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting water relations of three coastal tree species with different exposure to salinity

Abstract: This field study examined the ecophysiological responses of three tree species to salinity in the Austin Bay Nature Reserve, adjacent to the Peel-Harvey Estuary in Western Australia (115 46 0 E 32 37 0 S). The area is at increased risk of flooding with saline water during storm surges due to the construction of a channel between the estuary and Indian Ocean in 1994. Banksia attenuata R.Br. occurs on small sandy ridges adjacent to a seasonal wetland, while Melaleuca cuticularis Labill. and Casuarina obesa Miq. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 60 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…Firstly, C. obesa trees growing at Toolibin Lake are likely to be shallow‐rooted, as reflected in our study and shown by work on the same species in an estuarine ecosystem by Carter et al . (). A shallow root system will quickly intercept downward‐flowing water and, at Toolibin Lake, will be less prone to the effects of rising saline groundwater.…”
Section: Discussionmentioning
confidence: 97%
“…Firstly, C. obesa trees growing at Toolibin Lake are likely to be shallow‐rooted, as reflected in our study and shown by work on the same species in an estuarine ecosystem by Carter et al . (). A shallow root system will quickly intercept downward‐flowing water and, at Toolibin Lake, will be less prone to the effects of rising saline groundwater.…”
Section: Discussionmentioning
confidence: 97%
“…Leaf-specific conductivities of B. menziesii ranged from 0.9 × 10 −4 to 1.0 × 10 −3 kg m −1 MPa −1 s −1 . Water relations of B. menziesii are very similar to the co-dominant B. attenuata (Canham et al 2009) for which Carter et al (2006) found higher osmotic potential than in co-occurring woodland species and interestingly no osmotic adjustment between summer and winter (always higher than −3 MPa). However, the bulk elastic modulus was 28% higher during summer (less elastic cells) compared to winter suggesting that turgor maintenance relies on changes in cell wall elasticity rather than adjustments in osmotic potential.…”
Section: Diurnal Course Of Stomatal Conductance Patch Pressure Balamentioning
confidence: 68%
“…On the other hand, seasonal effects on plant growth and development may be difficult to detect in field studies where many other sources of variation cannot be controlled [4]. In this comparative study on Tamarix species, photosynthesis showed the most remarkable seasonal differences: T. arborea var.…”
Section: Discussionmentioning
confidence: 93%